Sex-specific differences in insulin resistance in type 1 diabetes: The CACTI cohort - Millstein, Richard J. (J Diabetes Complications, 2018)
OBJECTIVE: To test the hypothesis that multitissue deficits in insulin sensitivity are greater among women than men with type 1 diabetes compared to respective controls. RESEARCH DESIGN AND METHODS: Three-stage hyperinsulinemic-euglycemic clamps (4, 8, 40mU/m(2)/min) were performed on 41 people with type 1 diabetes and 47 adults without diabetes (mean±SD age 46±8). Infusions of [1-(13)C]palmitate, [1,1,2,3,3-(2)H(2)]glycerol, and [6,6-(2)H(2)]glucose isotope tracers were used to determine free fatty acid (FFA), glycerol, and glucose kinetics in 52 of these participants (25 M and 27 W). RESULTS: There was no difference in age or BMI by type 1 diabetes status in either sex. Free fatty acid rate of appearance (FFA Ra) was higher in both sexes with type 1 diabetes compared to those without diabetes during stages 1 and 2. The same was seen with glycerol for stages 1 and 2. During stage 3 glucose rate of disappearance (Rd) was lower in those with type 1 diabetes among both sexes. All had sex by type 1 diabetes interactions with greater deficits in insulin sensitivity in women. While there was no sex by diabetes interaction in regards to glucose rate of appearance (Ra), those with type 1 diabetes had a higher glucose Ra than those without diabetes. CONCLUSIONS: We found that type 1 diabetes affected adipose and skeletal muscle insulin sensitivity to a greater extent in women than in men, perhaps contributing to the greater relative increase in cardiovascular risk in women with type 1 diabetes.